Due Process in UN Commissions of Inquiry: A Legal Analysis of the Procedures of Goldstone's Gaza Inquiry. Issue 1 (1st January 2017) - Nesbitt, Michael
Abstract : Throughout its history, the United Nations has resorted to large-scale ad hoc Commissions of Inquiry (UN COIs) to investigate serious international incidents. These UN COIs have often been highly political affairs, though their tasks and goals—including most recently investigating reports of war crimes or crimes against humanity the world over—are distinctly legal in nature. The result has been a focus on both the politics of such UN COIs—including most prominently whether their mandates or their Commissioners are biased—and on the merit of their legal-criminal findings. Yet it is the processes and procedures of UN COIs, and particularly their commitment to transparent due process, that are best able to form a bulwark against both political and legal attacks. Thus, it is their processes and procedures that should be the focus of much legal-academic work; unfortunately, to date this has not tended to be the case. By analyzing perhaps the most well-known and controversial recent UN COI, the 2009 United Nations Fact Finding Mission on the Gaza Conflict, and focusing on its due process and procedures rather than its politics or its correct application of international criminal or human rights law, this paper seeks to remedy this oversight. It seeks to identify the legal and procedural shortcomings—the failures of due process—of a well-resourced, well-staffed political inquiry to offer a representative example of how UN COIs tend to fall short, why they must be considered legal undertakings, and how future UN COIs might remedy these common shortcomings by focusing on the legality of their procedures.